Reflection on Parenting Course Learning in Fostering Parent-Teacher Collaboration at PG-Paud UNIPAR Jember - Agus Salim (Publikasi Indonesia, 2025)
Parent-teacher collaboration remains a challenge in many early childhood education settings in Indonesia, necessitating early preparation for prospective teachers. This article aims to examine the role of parenting education in shaping prospective early childhood education (PAUD) teachers who are capable of bridging collaboration between parents and teachers. Using a reflective approach to the Parenting course taught in the Early Childhood Teacher Education Program (PG-PAUD) at UNIPAR Jember, this paper highlights the importance of integrating positive parenting values, empathetic communication, and strengthening the role of the family in the early childhood education process. The method employed is descriptive qualitative, based on classroom reflections and student assignments. The results show that students are able to understand and apply fundamental parenting principles and design simple programs that can be implemented in real contexts. This reflection is significant as it provides a concrete picture of students’ readiness to bridge communication gaps between families and educational institutions, and it illustrates the transformation of the PAUD teacher’s role as a facilitator, mediator, and learning partner for parents. The implication is that parenting education at the tertiary level needs to be continuously strengthened as an integral part of the PG-PAUD curriculum, both theoretically and practically.